Analysis of the Effect of Domestic Investment (PMDN), Number of Industrial Sectors, and Population on Gross Regional Domestic Product - Syarifah, Hidayatus; Primandhana, Wiwin Priana (Journal of Regional Economics and Development, 2026)
This study examines the impact of Domestic Direct Investment (PMDN), the number of industrial sectors, and the population on the GRDP of Sidoarjo Regency in the 2010-2023 period. Using a quantitative approach and multiple linear regression. The results of the study indicate that simultaneously the variables PMDN, the number of industrial sectors, and the population have a significant positive effect on the GRDP of Sidoarjo Regency. Together, these three variables have a significant impact on GRDP, but individually only the number of industrial sectors and the population have a significant impact on GRDP. This study recommends strengthening investment efficiency through supporting policies, maximizing the role of industry, and demographic management to support sustainable economic growth in Sidoarjo Regency.